Management of occupational exposure to blood and body fluids among health care workers in the National Hospital of Sri Lanka: an audit of practice - Vithana, V.H.; Weerakkody, M.I.; Pallewela, V.H.; Karunanayake, P.; Senarath, U.; Sheriff, M.H.R. (My University, 2005)
Occupational exposure to blood-borne viruses is an important issue for health care workers (HCWs). Guidelines for their management are known to be implemented sub optimally. Objectives: To assess the extent and pattern of occupational exposure to blood and body fluids among HCWs and their management, at the National Hospital of Sri Lanka (NHSL). Methods: Data were collected from nursing and medical staff regarding exposures occurring within the preceding 6 months, using a pre-tested, self-administered questionnaire. Results: 155 health care workers, 102 (65.9"10) nurses and 53 (34.2%) doctors, participated (response rate 55.36%). Needle stick injury was the commonest: 82 (59% of all injuries) among 60 HCWs. The least common was cuts with contaminated sharps (5.8 % of all injuries). Mean injury rate was 0.9 per person per 6 months. 69.81% of doctors and 38.23% of nurses had sustained at least one exposure. Nurses were more likely to wash/irrigate the injury site with water (p=0.024), report to the infection control unit (p=O.024) and seek further advice regarding the injury (p=O.043) than doctors. HIV antibody status of the patient was checked in 17.4% of the exposures. None received post exposure HIV prophylaxis. 89.2% of the exposures had had hepatitis B vaccination prior to the injury, but antibody levels were checked in only 11.5%. Conclusions: Occupational exposure to blood-borne viruses are common among HCWs and are commoner among doctors. Basic post-exposure management appears unsatisfactory, especially among doctors.